Evaluación del proceso de extracción y purificación del polímero poli(3-hidroxibutirato) P3HB obtenido de la cepa Burkholderia cepacia B27 con un solvente orgánico no halogenado (2019)
An alternative to conventional polymers are the polyhydroxyalkanoates (PHA) polymers synthesized by microorganisms, biodegradable and physico-chemical properties similar to the polymers derived from petroleum. The most studied PHA is poly(3-hydroxybutyrate) (P3HB) by thermal and mechanical properties similar to the polypropylene, but their high cost of production is a drawback for the production at industrial level. One of the methods more employees for the obtaining of PHA is one that involves a conventional solvents, solvent is chloroform, a volatile solvent, toxic and harmful to the health of who manipulates it, for this reason established a procedure for determining a solvent as an alternative to the conventional solvent which present an optimal recovery percentage evaluated various factors of concentration, temperature, time of agitation and type of solvent.